IMPELEMENTASI APLIKASI COREL DRAW DALAM MENINGKATKAN KEMAMPUAN DESAIN SISWA SMKN 1 PALIBELO - Jannah, Miftahul; Susi Sulastri; Nur Syari’ah; Faris Azis; Khairunnisa (Community : Jurnal Pengabdian Pada Masyarakat, 2024)
In the ever-growing digital era, graphic design skills are becoming increasingly important and in demand in various industries. Seeing the importance of building students' design abilities in terms of skills, it is necessary to implement design training using Corel Draw for students at SMKN 1 Palibelo. However, the obstacle currently faced by students at SMKN 1 Palibelo is their lack of interest in using design technology. This can be seen from some students who are still unable to create designs using Corel Draw. One effort to improve the design skills of students at SMKN 1 Palibelo is by implementing design training using the Corel Draw application. Therefore, the PKM Team held activities to implement Corel Draw design training at SMKN 1 Palibelo. This PKM aims to teach how to create a design systematically and structured using this application. The training provided includes an introduction to the basic tasks of Corel Draw and the tools contained in it. Next, how to practice making a simple poster design. Starting from making worksheet sizes, writing text, giving colors, the editing process to the design creation process. Comprehensively, the implementation of this training went smoothly. Indicators of success can be seen from the input given by the students who took part in this activity, which shows that the majority of students were able to understand the training process provided and also that the design making process was easy to put into practice.